Diminazene resistance in Trypanosoma congolense is not caused by reduced transport capacity but associated with reduced mitochondrial membrane potential. Issue 2 (18th May 2021) - Carruthers, Lauren V.; Munday, Jane C.; Ebiloma, Godwin U.; Steketee, Pieter; Jayaraman, Siddharth; Campagnaro, Gustavo D.; Ungogo, Marzuq A.; Lemgruber, Leandro; Donachie, Anne‐Marie; Rowan, Tim G.; Peter, Rose; Morrison, Liam J.; et al.
Abstract: Trypanosoma congolense is a principal agent causing livestock trypanosomiasis in Africa, costing developing economies billions of dollars and undermining food security. Only the diamidine diminazene and the phenanthridine isometamidium are regularly used, and resistance is widespread but poorly understood. We induced stable diminazene resistance in T. congolense strain IL3000 in vitro. There was no cross‐resistance with the phenanthridine drugs, melaminophenyl arsenicals, oxaborole trypanocides, or with diamidine trypanocides, except the close analogs DB829 and DB75. Fluorescence microscopy showed that accumulation of DB75 was inhibited by folate. Uptake of [ 3 H]‐diminazene was slow with low affinity and partly but reciprocally inhibited by folate and by competing diamidines. Expression of T. congolense folate transporters in diminazene‐resistant Trypanosoma brucei brucei significantly sensitized the cells to diminazene and DB829, but not to oxaborole AN7973. However, [ 3 H]‐diminazene transport studies, whole‐genome sequencing, and RNA‐seq found no major changes in diminazene uptake, folate transporter sequence, or expression. Instead, all resistant clones displayed a moderate reduction in the mitochondrial membrane potential Ψm. We conclude that diminazene uptake in T. congolense proceed via multiple low affinity mechanisms including folate transporters; while resistance is associated with a reduction in Ψm it is unclear whether this is the primary cause of the resistance. Abstract : Resistance to diminazene is one of the main problems facing the control of the livestock disease Animal African Trypanosomiasis (AAT, or nagana), caused by the parasite Trypanosoma congolense . We investigated the adaptations of the parasite that allow it to resist the drug and find that changes to the mitochondrion, where the parasite produces its energy, are the likely cause of the resistance. There was no change in drug uptake.